INTERAKSI DEWAN KOMISARIS INDEPENDEN DENGAN KINERJA KEUANGAN TERHADAP INCOME SMOOTHING (STUDY PADA PERUSAHAAN PROPERTY DAN REAL ESTATE) - Jepri Parningotan Sianturi, Jepri; Suratno; JMV, Mulyadi (SEKOLAH PASCASARJANA PRESS, 2019)
The purpose of this study is to test whether the variable profitability and financial leverage affect the practice of income smoothing, and test whether the variable profitability and financial leverage moderated by the board of independent commissioners affect the practice of income smoothing. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange, while the object of research (samples) as many as 158 data. The technique of determining the sample using purposive sampling method. Data were tested using binary logistic regression. The result of the research shows that profitability has significant effect to income smoothing, financial leverage has no effect on income smoothing, profitability moderated by independent board of commissioner has significant negative effect to income smoothing, and financial leverage moderated by independent board of commissioner has no effect to income smoothing.